2012 14th International Conference on Transparent Optical Networks (ICTON) 2012
DOI: 10.1109/icton.2012.6253868
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength regeneration of phase encoded signals based on phase sensitive amplifiers

Abstract: Future high capacity optical links will have to make use of frequent signal regeneration to enable long distance transmission. In this respect, the role of all-optical signal processing becomes increasingly important because of its potential to mitigate signal impairments at low cost and power consumption. More substantial benefits are expected if regeneration is achieved simultaneously on a multiple signal band. Until recently, this had been achieved only for on-off keying modulation formats. However, as in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…where θ = θ1 + θ2 − K1L1. Thus, the PSA gain G de-pends upon signal phase only and hence two pumps and input signal need not be synchronized by phase locking, which is otherwise a difficult process to achieve in optical domain (22,29). It is also observed that PSA gain depends upon amplifier length (HNLF2 length), nonlinear coefficient (γ ) and pump powers.…”
Section: Solving Fwm In Hnlfmentioning
confidence: 99%
See 1 more Smart Citation
“…where θ = θ1 + θ2 − K1L1. Thus, the PSA gain G de-pends upon signal phase only and hence two pumps and input signal need not be synchronized by phase locking, which is otherwise a difficult process to achieve in optical domain (22,29). It is also observed that PSA gain depends upon amplifier length (HNLF2 length), nonlinear coefficient (γ ) and pump powers.…”
Section: Solving Fwm In Hnlfmentioning
confidence: 99%
“…More-over, pump waves are also present at the output of PSA, in addition to amplified signal, which acts as classical noise source. In frequency degenerate, PS-FOPA signal and idler are present at the same frequency, hence there is no shift in operating frequency (4,22,23). However, in this technique, an optical phase locking between signal and pump waves is required.…”
Section: Introductionmentioning
confidence: 99%
“…All-optical signal regeneration is the key technology to improve the signal quality by restoring the original shape of the optical signals [8]. All optical regeneration results in reduction of noise in the optical signals for high capacity optical links at a low cost and low power consumption [9]. Based upon their functionality, optical regenerators are generally of two major types that are 2R-and 3R-regenerators.…”
Section: Introductionmentioning
confidence: 99%